Commercialization of CIAT's Urochloa hybrids (e.g. Mulato II, Cayman, Cobra) through private sector partner - CGIAR Research Program on Livestock (2018)
Evidence for 2018 is not yet available. Precise information on seed sales is expected to be received from Papalotla by June 2019. However, informal information from Papalotla indicates that an additional 100,000 hectares have been reached in 2018 (the 100,000 hectares per year are cumulative).